If it's not what You are looking for type in the equation solver your own equation and let us solve it.
25-x-19=26-5x-6x
We simplify the equation to the form, which is simple to understand
25-x-19=26-5x-6x
We move all terms containing x to the left and all other terms to the right.
-1x+5x+6x=+26-25+19
We simplify left and right side of the equation.
+10x=+20
We divide both sides of the equation by 10 to get x.
x=2
| 7x^7-56x^6+42x^5= | | 165-7x=20x+15 | | 10-10x=118-38x | | 2x-x+8x= | | 179-5x=6x+14 | | 9(x-3)+8(x+6)=4(8-7x) | | 0.1(x+100)+0.1x=1 | | -1*[-2]=x | | -36-2x+9x=3x+12 | | 5(t-2)-3t=4(2+4)-9 | | 4(2x+9)=20 | | 8a^2+4a= | | 9+n=2n-4 | | 9-10x=94-45x | | (x+2)(2x-3)=0 | | 4x-11x+7=4 | | 5(x+2)+x=3(x-1)+1 | | 24+0.99x=1.49x | | 4(v-3)-6v=-2(v+6) | | 15=-8(c-1)+9 | | x^6-9x^3+20=0 | | 4(v-3)-6v=2(v+6) | | 5(2+y)-y=10+4(y+1) | | 8(2x+3)=56 | | 4x^3+22x^2+52x=0 | | 7(2k-1)+4=7 | | -2(w+4)+6w=4(w-3) | | -x+3=9 | | 5(2x+3)=45 | | -4(v+3)-3v=2(v+3) | | -2(x+4)+6w=4(w-6) | | 12-C+15-C=7 |